Pleural Empyema due to Group D Salmonella - Jennifer C. Kam; Sami Abdul-Jawad; Chintan Modi; Yazan Abdeen; Fady Asslo; Vikram Doraiswamy; Joseph R. DePasquale; Robert S. Spira; Walid Baddoura; Richard A. Miller (Case Reports in Gastrointestinal Medicine)
Non-typhi Salmonella normally presents as a bacteremia, enterocolitis, and endovascular infection but rarely manifests as pleuropulmonary disease. We present a case of a 66-year-old female with underlying pulmonary pathology, secondary to an extensive smoking history, who presented with a left-sided pleural effusion. The causative agent was identified as being group D Salmonella. Decortication of the lung was performed and the patient was discharged on antibiotics with resolution of her symptoms. This case helps to support the inclusion of Salmonella group D as a possible etiological agent of infection in the differential causes of exudative pleural effusions.